2020
DOI: 10.3389/fbioe.2020.00638
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Harmonic Indexes of the Arterial Blood Pressure Waveform in Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is an important public health issue worldwide. T2DM correlates with cardiovascular disease. Arterial stiffness is also a key factor that can be thought of as a surrogate marker. Nevertheless, it was unclear which harmonic indexes of blood pressure waveforms (BPWs) from subjects' radial artery pulses would be affected by T2DM. Therefore, the objective of this study was to investigate whether and how harmonic indexes can be used to discriminate hemodynamic differences between pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In addition, we established a five-step HA computation formula for the peripheral volume pulse, described in Section 2.3.2. Hence, the current study obtained results for type 2 diabetes mellitus [14][15][16][17]. It has been reported that the fourth harmonic component of the radial pulse wave is important for the risk assessment of macrovascular and microvascular events in patients with type 2 diabetes [14], cardiovascular risk [15], and arterial blood pressure waveforms [16], with different radial pulse wave harmonic indices, silent coronary artery disease, and adverse cardiac events [17].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In addition, we established a five-step HA computation formula for the peripheral volume pulse, described in Section 2.3.2. Hence, the current study obtained results for type 2 diabetes mellitus [14][15][16][17]. It has been reported that the fourth harmonic component of the radial pulse wave is important for the risk assessment of macrovascular and microvascular events in patients with type 2 diabetes [14], cardiovascular risk [15], and arterial blood pressure waveforms [16], with different radial pulse wave harmonic indices, silent coronary artery disease, and adverse cardiac events [17].…”
Section: Discussionmentioning
confidence: 72%
“…It has been reported that the fourth harmonic component of the radial pulse wave is important for the risk assessment of macrovascular and microvascular events in patients with type 2 diabetes [14], cardiovascular risk [15], and arterial blood pressure waveforms [16], with different radial pulse wave harmonic indices, silent coronary artery disease, and adverse cardiac events [17]. Therefore, our findings for synchronous peripheral volume pulses are consistent with the findings in [14][15][16][17], in which the radial pulse wave was adopted with different harmonic coefficients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heart, as a positive displacement pump, drives arterial flow by a multiharmonic pressure waveform that is known to correlate with physiologic and pathologic processes and conditions 1 4 . Downstream from the heart, as blood flows through the anatomically sophisticated arterial network 5 , it exhibits complex hemodynamic features such as coherent structures 6 , helical flow (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The heart, as a positive displacement pump, drives arterial flow by a multiharmonic pressure waveform that is known to correlate with physiologic and pathologic processes and conditions [1][2][3][4] . Downstream from the heart, as blood flows through the anatomically sophisticated arterial network 5 , it exhibits complex hemodynamic features such as coherent structures 6 , helical flow (i.e.…”
Section: Introductionmentioning
confidence: 99%